Analisis Program Pojok Literasi Dalam Era Digital di SD Mujahidin Pontianak - Dewi, Ria Meylistifa (Jurnal Didaktika Pendidikan Dasar, 2025)
In today’s digital era, literacy is a critical competency learners must possess. One way to improve learners’ literacy is to implement a literacy corner program in schools. The literacy corner program is an activity that provides a classroom corner for students to read and learn. This research aims to explain how the literacy corner program in the digital era at SD Mujahidin Pontianak. This research used a qualitative case study approach with teachers and students as research subjects. Research data were obtained through observation and interviews. The results showed that the literacy corner program at SD Mujahidin Pontianak is still running but needs improvement. The literacy corner program is considered not very effective at increasing students’ interest in reading due to the influence of technology, specifically gadgets. Gadgets have a bad influence on students’ interest in reading. Overall, the literacy corner program is considered effective in improving learners’ literacy in the digital era.